Bank financing and credit ratings. Issue 12 (11th July 2020) - Bedendo, Mascia; Siming, Linus
ABSTRACT: By looking at a sample of firms rated by S&P, we study the extent to which the mix between bank financing and other sources of debt affects corporate credit ratings. We find that S&P penalizes firms of high credit quality that use relatively more bank debt compared to market debt. Instead, debt composition does not seem to matter when rating risky firms. We conclude that managers of firms of high credit quality should have relatively low (high) recourse of bank financing (public debt) from a credit ratings perspective.